Border City as Subject Matter: Ethnographic Reflections from a Maritime Borderland in Indonesia - Afrida, Afrida; Jonson Handrian Ginting (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2025)
This study examines Tanjungbalai, a border city on the eastern coast of Sumatra, as an active producer of border practices rather than a passive periphery of the Indonesian state. Using long-term ethnographic fieldwork involving participant observation, in-depth interviews, and documentary analysis, the research reveals how residents negotiate and reinterpret state boundaries in their everyday lives. The findings show that the city’s spatial orientation is fundamentally maritime: informal ports (tangkahan) function as the true centers of mobility and trade, embodying deliberate strategies of spatial illegibility that resist state surveillance. The informal economies of undocumented motorcycles and used clothing further demonstrate how activities deemed illegal by the state become locally licit within a moral economy shaped by survival and limited formal opportunities. Dense transnational kinship networks linking Indonesia and Malaysia act as critical urban infrastructure, circulating capital, labor, and protection across the strait. At the same time, the region’s porosity has enabled the rise of large-scale narcotics trafficking and digital fraud, positioning the city within broader criminal geographies. Overall, the study argues that Tanjungbalai is a dynamic social laboratory where legality, mobility, and identity are continuously contested and remade.